2021
DOI: 10.3390/molecules26195950
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and Molecular Engineering of Glycan Sialylation in Heterologous Systems

Abstract: Glycans have been shown to play a key role in many biological processes, such as signal transduction, immunogenicity, and disease progression. Among the various glycosylation modifications found on cell surfaces and in biomolecules, sialylation is especially important, because sialic acids are typically found at the terminus of glycans and have unique negatively charged moieties associated with cellular and molecular interactions. Sialic acids are also crucial for glycosylated biopharmaceutics, where they prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 141 publications
0
10
0
Order By: Relevance
“…More than half of the proteins in organisms have glycosylation modification, including transcription factors and metabolism-related enzymes ( Ferreira et al, 2021 ; Sun et al, 2021 ; Zheng et al, 2021 ). Glycosylation modification affects protein spatial conformation, activity, transportation, and positioning and is widely involved in intercellular recognition, regulation, and signal transduction ( Hombu et al, 2021 ). Protein glycosylation has been proved to play an important role in the occurrence and progression of various metabolic diseases ( Dozio et al, 2021 ) and malignant tumor diseases ( Reily et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…More than half of the proteins in organisms have glycosylation modification, including transcription factors and metabolism-related enzymes ( Ferreira et al, 2021 ; Sun et al, 2021 ; Zheng et al, 2021 ). Glycosylation modification affects protein spatial conformation, activity, transportation, and positioning and is widely involved in intercellular recognition, regulation, and signal transduction ( Hombu et al, 2021 ). Protein glycosylation has been proved to play an important role in the occurrence and progression of various metabolic diseases ( Dozio et al, 2021 ) and malignant tumor diseases ( Reily et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, flow cytometry analysis revealed that Ac 4 ManN-DNP treatment also failed to yield the surface presentation of glycans modified with DNP hapten on cancer cells, unlike the two-step labeling with Ac 4 ManNAz and DBCO-DNP (Figure 4e). A series of enzymatic reactions are required to convert the derivatives of ManNAc into sialic acids, which are then incorporated into the nonreducing termini of N-glycans 23 (Figure 5a). Given that our above-described results suggested that hapten-modified ManNAc derivatives may not be suitable substrates for the initial enzymatic reactions, we synthesized two hapten-conjugated sialic acid derivatives, fluorescein isothiocyanate-conjugated sialic acid (Sia-FITC) and dinitrophenyl-conjugated sialic acid (Sia-DNP), 24,25 (Figure 5b,c) to bypass the initial enzymatic steps.…”
Section: ■ Resultsmentioning
confidence: 99%
“…Similarly, low fulfillment is seen in high-yield expression systems 87 necessitating, in some cases, supplementation with maturing glycoenzymes. 8890…”
Section: Discussionmentioning
confidence: 99%